Innovative Curricula with Social Impact: The Integrality of substantive functions - Imperatore, Simone (2023)
Bibliographic, descriptive and prospective, this essay aims to point out possibilities and challenges in the implementation of the curricularization of the university-society linkage function, as it is called at the National Autonomous University of Honduras (UNAH), in dialogue with the epistemologies and Latin American experiences and in line with the studies of Freire, Tommasino, Imperatore, Tobón, Castro, among others. It is instituted as a subsidy for the ongoing discussions with a view to the systematization and institutionalization of the curricular trajectories in the UNAH careers, guided by the critical extension model. Its main characteristics are the integrality of substantive functions; socio-educational, socio-community and socio-productive practices related to the Honduran reality; interdisciplinarity and interprofessionality; influence academic training and impact and social transformation. He points out as common challenges, based on dialogue with teachers and administrators, the need to collaboratively develop new pedagogical architectures based on socio-critical, holistic and postmodern epistemologies, using dialogue within the university as a work methodology, integrating teaching pedagogical teams, research and outreach, in articulation with the different actors and social sectors. The definition of comprehensive practices, in turn, constitutes the founding axis of the trajectory to implement the proposed change, in addition to the redefinition of the concept of linkage and the necessary elimination of hierarchical barriers within careers and/or disciplinary boundaries. No less important, it is necessary to deepen the discussion on evaluation methodologies and processes consistent with such epistemologies and architectures. In the field of management, issues such as overcoming the culture of isolated work and reducing the distance between academic and management processes should be addressed. The need to strengthen cooperative and integrated work dynamics in the institutions and between them and their territory, the compatibility of academic and social times, the regulation of activities and curricular integration trajectories, are also part of the list of challenges to overcome. Even so, the limited sources of funding, the logistical difficulties, and the lack of openness of teachers to the proposed change are signs of a long way to go.